Lost in action: Climate friendly use of European peatlands needs coherence and incentive-based policies. Issue 145 (July 2023) - Chen, Cheng; Loft, Lasse; Matzdorf, Bettina
Abstract: Peatlands are significant to global efforts to combat climate change. However, to date, they have been a missing piece in the climate change mitigation policy puzzle in the European Union (EU). Taking a policy coherence perspective, we investigate how policies from different governance levels—that is, EU, member state, and regional levels—support and impede existing and new policies for climate-friendly peatland usage. We put a particular focus on incentive-based policy instruments, because such incentives are often advocated as promising policy instruments for supporting the transition to the sustainable management of peatlands. We selected the three peatland-rich EU countries Finland, Germany, and the Netherlands. Based on semi-structured interviews with 35 experts, we indicate a lack of horizontal policy coherence between agriculture, nature conservation, water management, forestry, energy, and climate policies in terms of climate change mitigation measures on peatlands. At the EU level, most prominently, the Common Agricultural Policy counteracts climate targets because direct payments currently encourage the unsustainable management of peatlands. At the national and subnational levels, water quality in Finland, nature conservation in Germany, and subsidence in the Netherlands were primary objectives of peatland relevant policies. Due to a lack of clear guidance on raising the groundwater table, the current incentive-based policy instruments are ineffective for reducing emissions. Despite its higher mitigation potential, potential incentive-based policies for rewetting encounter various regulatory barriers caused by the policy incoherence. We conclude that the transition to climate-friendly peatland usage requires coherent regulatory frameworks and incentive-based policies supporting rewetting. Highlights: We demonstrate the multi-sectoral and multi-level nature of peatland policies in the EU. Agriculture, nature, water, and energy policies often impede horizontal coherence. Conflicts between EU, national, and regional policies hinder vertical coherence. Regulatory frameworks and incentive-based policies should be coherent. Current incentive-based policy instruments are ineffective for emissions reduction.